Whole-genome sequencing and secondary metabolite exploration of the novel Bacillus velezensis BN with broad-spectrum antagonistic activity against fungal plant pathogens - Zheng, Yanli; Liu, Tongshu; Wang, Ziyu; Wang, Xu; Wang, Haiyan; Li, Ying; Zheng, Wangshan; Wei, Shiyu; Leng, Yan; Li, Jiajia; Yang, Yan; Liu, Yang; et al. (Frontiers in Microbiology, 2025)
The utilization of chemical pesticides recovers 30%−40% of food losses. However, their application has also triggered a series of problems, including food safety, environmental pollution, pesticide resistance, and incidents of poisoning. Consequently, green pesticides are increasingly seen as viable alternatives to their chemical counterparts. Among these, Plant Growth-Promoting Rhizobacteria (PGPR), which are found within plant rhizosphere, stand out for their capacity to stimulate plant growth. Recently, we isolated a strain, BN, with broad-spectrum antimicrobial activity from the rhizosphere of Lilium brownii. Identification revealed that this strain belongs to the species Bacillus velezensis and exhibits significant inhibitory effects against various fungal plant pathogens. The complete genome sequence of B. velezensis BN consists of a circular chromosome with a length of 3,929,791 bp, includes 3,747 protein-coding genes, 81 small RNAs, 27 rRNAs, and 86 tRNAs. Genomic analysis revealed that 29% of the genes are directly involved in plant growth, while 70% of the genes are indirectly involved. In addition, 12 putative biosynthetic gene clusters were identified, responsible for the synthesis of secondary metabolites, such as non-ribosomal peptides, lanthipeptides, polyketides, siderophores, and terpenes. These findings provide a scientific basis for the development of efficient antimicrobial agents and the construction of biopesticide production platforms in chassis cells.